Pengembangan Edu-Ekowisata Hutan Mangrove Jembatan Pelangi Desa Lontar Kecamatan Tirtayasa Kabupaten Serang - Fitri Ratnasari; Agung Setyo Sasongko; Ahmad Satibi (Samakia : Jurnal Ilmu Perikanan, 2024)
Ekowista mangrove Rainbow bridge is located in Lontar Village, Tirtayasa District, Serang Regency, Banten Province. Ecotourism has the potential that needs development with a development strategy, a development strategy is needed with many problems that are seen directly. With this, researchers in research on the Development of Mangrove Forest Edu-Ecotourism, Rainbow Bridge, Lontar Village, Tirtayasa District, Banten. Researchers have 2 objectives, namely Analyzing the suitability of mangrove ecotourism land, Rainbow Bridge, Lontar Village, Tirtayasa District, Recommending mangrove ecotourism development strategies as education-based and sustainable ecotourism. The method used in this study is Qualitative with Descriptive Qualitative research design and the instruments used are Observation, Interview, and Document Study. Data collection using primary data taken directly at the research location and secondary data obtained from journals, books and local governments. Further rare SWOT analysis is carried out with data that has been found through observation, interviews and document studies. The development that is the result of this research is in the form of adding and improving ecotourism supporting facilities and infrastructure, cooperation between managers, the government and the surrounding community in the development of love bridges, adding mangrove trees with more types, increasing the Tourism Compatibility Index and maintaining existing facilities.